2019
DOI: 10.1002/jcsm.12472
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone therapy induces molecular programming augmenting physiological adaptations to resistance exercise in older men

Abstract: BackgroundThe andropause is associated with declines in serum testosterone (T), loss of muscle mass (sarcopenia), and frailty. Two major interventions purported to offset sarcopenia are anabolic steroid therapies and resistance exercise training (RET). Nonetheless, the efficacy and physiological and molecular impacts of T therapy adjuvant to short‐term RET remain poorly defined.MethodsEighteen non‐hypogonadal healthy older men, 65–75 years, were assigned in a random double‐blinded fashion to receive, biweekly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 113 publications
(212 reference statements)
4
85
2
1
Order By: Relevance
“…Reports indicated that T can increase muscle mass and decrease the amount of fat in a dose-dependent manner in young and older men [6,9,21]. The increase in muscle mass was due to hypertrophy of myofibers with response to T [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports indicated that T can increase muscle mass and decrease the amount of fat in a dose-dependent manner in young and older men [6,9,21]. The increase in muscle mass was due to hypertrophy of myofibers with response to T [13].…”
Section: Discussionmentioning
confidence: 99%
“…T and its synthetic homologues have been used clinically and illegally to increase muscle mass [6,22]. In response to T administration, the number of proliferating cell nuclear antigen (PCNA) positive satellite cells increased in human skeletal muscle [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that lean mass gains were not evident in our older participants, and work from our lab shown this may indeed be due to anabolic resistance [ 37 ], which itself is multi-faceted (reduced translational capacity, hormonal efficiency and MPS with increased MPB), however RET still remains the most effective method of counteracting the age-related declines in loss of lean mass [ 38 ], particularly if it is combined with, for example, exogenous testosterone administration [ 39 ] or protein supplementation [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although testosterone supplementation in older men has been shown to improve body composition, yet the effects on muscular strength or physical function are still conflicting (Endo et al, 2020). It has been shown that testosterone replacement therapy does not offer any benefit beyond resistance exercise alone in elderly patients with low to normal serum testosterone, but may be an effective short-term intervention to overcome age-related deficits in adaptive responses to resistance training (Gharahdaghi et al, 2019). However, because of potential adverse events, the clinical meaningfulness of testosterone in the management of sarcopenia should be carefully evaluated.…”
Section: Recommendations For the Management Of Sarcopeniamentioning
confidence: 99%